Water quality and disinfection impact of ClO2 contamination by free chlorine: A case study. Issue 2 (1st March 2004) - Hofmann, Ron; Andrews, Robert C; Ranger, Georges
Abstract : A bench-scale study was conducted using water from a drinking water treatment facility on Lake Ontario to investigate water quality and disinfection impacts of chlorine contamination in a chlorine dioxide solution applied for primary disinfection. Levels of chlorine contamination were varied between 0% (pure chlorine dioxide) and 20%, with a chlorine dioxide dose of 1 mg/L. The chlorine did not significantly affect the rate of chlorine dioxide decay in the water. The chlorine reduced chlorite formation, but led to a corresponding increase in chlorate formation. Trihalomethane and haloacetic acid concentrations varied with the amount of free chlorine present in the chlorine dioxide solution. Levels of Bacillus subtilis endospore inactivation were similar for solutions containing pure chlorine dioxide and a 20%:80% chlorine:chlorine dioxide mass ratio (for the same total chlorine concentration). Since chlorine alone has been reported to be very ineffective against these endospores, the results suggest that the disinfection effectiveness of the mixture was greater than the effectiveness predicted from each of the two disinfectants acting alone. Key words : chlorine dioxide, chlorine, disinfection, by-products, inactivation, drinking water.